Experimental and Numerical study of Turning Cutting Tools Random Vibration Towards Mitigation - A. Bedaiwi, Bashar (Journal of Engineering and Sustainable Development, 2013)
Turning machine vibration is an old problem on manufacturing processes. Unless avoided, vibrations may cause large dynamic loads damaging the machine spindle, cutting tool, or work-piece and leave behind a poor surface finish. This work intended mainly to measure the random vibration in various cutting tool length . Accelometer fixed in different points along the tool-piece to test the effect of distance from the fixed point on random vibration . A USB vibration analyzer and using a specialized program the data obtained analyzed for many random vibrational parameters (acceleration RMS, velocity RMS ,displacement RMS and maximum frequency ) .Different speed for the turning process are used (40 ,125,180 and 540 rpm ) .Result shows increasing behavior for acceleration , velocity and displacement with decreasing behavior upon decreasing distance from fixation point and decreasing behavior for maximum frequency reached. Also, a Finite element model was suggested using ANSYS 14 to simulate the cutting tool displacement and von-Miss stress distribution .